Concise and Environmentally Friendly Asymmetric Total Synthesis of the Putative Structure of a Biologically Active 3-Hydroxy-2-piperidone Alkaloid - Romero-Ibañez, Julio; Cruz-Gregorio, Silvano; Quintero, Leticia; Sartillo-Piscil, Fernando (Synthesis, 2018)
An asymmetric total synthesis of stereoisomers of a putative structure of 3-hydroxy-2-piperidone alkaloid derivative is described. This route is not only concise and efficient but also is achieved under an environmentally friendly approach. To this end, a direct and double C–H oxidation reaction of simple benzylated piperidine and Baker’s yeast reduction of a carbonyl group allowed the rapid access to the optically enriched (S)-1-benzyl-3-hydroxy-2-piperidone in only three steps. The NMR data agreed with those obtained in the first total synthesis (and in discrepancy with the natural product), however, optical rotation did not match with both neither the natural and synthetic material.
Keywords: alkaloids; 3-hydroxypiperidin-2-ones; total synthesis; environmentally friendly; TEMPO; C–H oxidation; sodium chlorite